Photocatalytic deconstructive aliphatic carbon–carbon bond cleavage and functionalization of unactivated alcohols - Thanetchaiyakup, Adisak (2023)
Carbon–carbon (C–C) bonds are challenging to selectively cleave owing to their chemical inertness and omnipresence in organic molecules; however, they can be targeted during the late-stage modification of natural products and active pharmaceutical ingredients. Herein, we report a selective deconstructive C(sp3)–C(sp3) bond cleavage and difunctionalization of unactivated alcohols mediated by a vanadium visible-light photocatalyst under ambient temperatures and pressures. Our base metal photocatalyst operates via ligand-to-metal charge transfer followed by an inner-sphere C–C bond cleavage to generate alkyl radicals that are trapped with SOMOphiles. We achieved 10 different bond formations on 44 examples using a range of commercially sourced alcohols, including natural products and biomolecules. Our protocol can also be used for the regio- and diastereoselective cyclization to form an α-aminolactone, and for the late-stage functionalization of bioactive oligopeptides to access unnatural amino acid residues.